The Effect of Using Interactive Electronic Module with Contextual Approach on Students Learning Motivation on Conductor and Insulator Materials - Fitria Lafifa; Dadan Rosana; Jumadi Jumadi; Suyanta Suyanta; S Nurohman; Sri Rejeki Dwi Astuti (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to develop an interactive electronic module product with a contextual approach and determine the effect of its use on students' learning motivation on conductor and insulator material. This study uses the R&D method with a 4D model. The research instrument is a questionnaire. The product was tested for feasibility, material validity, readability test, and measurement of student's learning motivation. The research subjects were seventh-grade students of MTsN 8 Banyuwangi and 5 validators. Data were analyzed qualitatively. The results of the study are the average product score is 3.9 with very good criteria and the percentage of 98% is very feasible, the validity of the material with a score of 3.8 with very good criteria and the percentage of 95% is very valid, the readability test obtained a score of 3 with very good criteria and percentage of 75% and learning motivation of students obtained a score of 3 and a percentage of 100% with high criteria. It can be concluded that the contextual approach interactive electronic module affects students' learning motivation on conductor and insulator material